Solvent-free sonochemistry as a route to pharmaceutical co-crystals. Issue 38 (23rd April 2019) - Roy, David; James, Stuart L.; Crawford, Deborah E.
Abstract : Using solvent-free sonochemistry to prepare pharmaceutically relevant co-crystals. Abstract : We describe the synthesis of pharmaceutically relevant co-crystals by solvent-free sonochemistry starting from solid reagents. Employing a standard ultrasonic cleaning bath, quantitative conversions occurred within 20–60 minutes to give co-crystals of paracetamol and aspirin with a range of co-formers. As well as the utility of the method, the work raises interesting mechanistic questions regarding acoustic cavitation with no liquid phase being present.